Catasetum × grasineideae (Orchidaceae: Catasetinae), a new nothospecies from Brazilian Amazon and taxonomic notes for the genus - Krahl, Dayse Raiane Passos; Schmal, Philippe; Chiron, Guy; Da Silva, João Batista Fernandes; Krahl, Amauri Herbert; Cantuária, Patrick De Castro (Phytotaxa, 2023)
Hybridization is a process that can occur randomly in nature between different genetically compatible species, as is observed within the genus Catasetum. Thus, this work proposes the description of a new nothospecies found in the lake of Castanho located in the municipality of Careiro Castanho. It is described, illustrated and compared with its parental species: C. gnomus and C. saccatum. In addition, information regarding the distribution, habitat and phenology as well as a key to the natural hybrids occurring in the Brazilian state of Amazonas are presented. Taxonomic notes are presented for five taxa of the genus currently treated as species that, after performing controlled pollination and germination in vitro, have proven to be in reality natural hybrids. Finally, we propose to place C. sanguineum into the synonymy of C. naso.